วาทกรรมวิเคราะห์พระราชนิพนธ์เรื่องพระมหาชนก - ณัฐพงค์ แย้มเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This research had as its main purpose to study the discourse in the composition of His Majesty the King’s "MAHAJANAKA". The study investigated the content as well as illustrated pictures and the reader’s comprehension. The procedures of the research were qualitative using multiple methodology comprising documentary research, textual analysis, in-depth interview, focus group interview and survey research. The research indicated that the success of his majesty’s MAHAJANAKA was due to the power of the discourse - both clear and hinting. The power of discourse was related to religion, sovereignty, economy, society and culture. Therefore, His Majesty’s composition "MAHAJANAKA" was accepted and widespreadly publicized". His majesty’s composition had made some adaptations in the last part of the narration, which was consistent with the comprehension of the people at present and an appropriation of current events. Besides that, MAHAJANAKA had aimed to focus on the country’s development and to reflect the author’s characteristics in the cast of the play. The result of the research indicated that the readers in this research gave a big welcome to His Majesty’s composition MAHAJANAKA but did not comprehend the real message. In the case of the students being assigned to read the book, it was found that they had a better understanding than those who voluntarily read it themselves.